Prokuratura Europejska - czy stanie się faktem? - Grzelak, Agnieszka (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The idea of the European Public Prosecutor dates from the 1990 s. Since then, the work on the creation of the foundations of the European Penal Code is associated with the necessity to strengthen the protection of the financial interests of the European Union, in particular the need to combat offences against those interests. Initially the Code seemed to be a purely theoretical concept that cannot be implemented into the EU legislative action because of the existing rules of conferral of powers and the lack of a legal basis for the establishment of such an office. However, with the entry into force of the Treaty of Lisbon the situation has changed, particularly with the addition of the Article 86 of the Treaty on the Functioning of the European Union (TFEU). As a result, the European Commission presented in July 2013 a draft regulation which should serve as a basis for establishment of the European Prosecutor Office [COM(2013) 534 final]. The aim of this paper is to present and briefly analyse major provisions of the proposed regulation, as well as objections submitted by national parliaments and doctrine, and finally the prospects of further work on the project. The discussion has not been yet completed because the draft has not been formally adopted yet and probably in the proposed form will not be accepted by all Member States, which will result in the implementation of the enhanced cooperation procedure.